Effect of Quality Products and Brand Image on Purchasing Decisions Through Interest to Buy Fertilizer Npk Custom PT. Fertilizer Kujang Cikampek - Aryadinata, Rendi; Rianto, Muhammad Richo (Journal of Scientific Research, Education, and Technology (JSRET), 2023)
Study this used for measure influence quality product and image brand to decision purchase through interest buy on custom NPK fertilizer PT. Fertilizer Kujang Cikampek . Study this is study quantitative where object used _ farmers use _ custom NPK fertilizer PT. Fertilizer Kujang Cikampek . Study this conducted with technique nonprobability sampling with method purposive sampling . As for the amount sample used _ in study this were 95 respondents. The design used in study this is testing hypothesis ( hypothesis testing ) with use structural equity model (SEM) – SmartPLS 4.0. Research results this give explanation that variable quality product no influential to decision purchase , however quality product to interest buy effect . Variable image brand influential to decision purchase and interest buy . Interest to buy influential to decision purchase as well as interest buy could mediate Among quality product to decision purchase and interest buy too _ mediate image brand to decision purchase. Study this own limitations object research that only done on the user custom NPK fertilizer PT. Fertilizer Kujang Cikampek . this _ as a suggestion for researcher next. renewal in study this combine variable quality product and image brand to decision purchase through interest buy .